UPAYA PENANGANAN GANGGUAN KESEHATAN MENTAL DI PROVINSI GORONTALO - Hakim, Lukman Nul (Jurnal Aspirasi, 2012)
Gorontalo is one of the youngest provinces in Indonesia. As a new province Gorontalo is facing problems of public service infrastructure, including those to manage the mental health problems. This research tries to find out how the local government of Gorontalo manages to solve all the problems despite the limitations. Method of literature review and in-depth interview has been used to find the answer for the two research questions: how the local government of Gorontalo manage the mental health problem? And what ought to be done so that mental health issue can be managed properly? Researcher found that the province health service has listed people with severe mental health problem from each municipality and give them haloperidol medicine. Unfortunately all those actions is thanks to the special program from Ministries of health (center government), not the initiative from the local government. The State should therefore propose a bill to force the local government to pay more attention to the mental health problem.